Ethnomodelling pada Konstruksi Atag di Desa Ajung Kabupaten Jember - Yusfan Adeputera Yusran; Sri Utami; Surjono; Atsar Yaisy Muhammad (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Atag functions as a place for the air curing process to dry tobacco leaves. This building, which is made of bamboo, has existed in Indonesia since 1850 and used to produce authentic quality cigars. Initially, this building was only utilized for local materials, however, based on the shape, dimensions, and construction, there is a tendency for atag to be established by considering several technical aspects. Therefore, this study aims to examine the technical ideas, such as calculations, practices, and procedures for making Atag using the ethnomodelling strategy. The results showed that the community's practices and calculations in building atag were a logical response in adapting to natural conditions such as climate, wind, and humidity. It also provided intelligence in utilizing the potential of local materials such as bamboo and sugarcane leaves